2005
DOI: 10.1007/s00701-004-0480-4
|View full text |Cite
|
Sign up to set email alerts
|

Improved brain protection at decompressive craniectomy – a new method using Palacos⌖ R-40 (methylmethacrylate)

Abstract: A new method is described for protecting the brain after decompressive craniectomy in which a temporary methylmethacrylate flap is formed, somewhat larger than the original bone flap, thus gaining "extra" volume for the oedematous brain in which to expand. The present procedure was developed as a part of ordinary clinical practice particularly in response to demands from the NICU staff and our colleagues at other clinics who were responsible for the care of the patient in the post NICU period. They made us kee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…There is a paucity of literature addressing any adverse effects of brain compression through cranial defects in general, with only theoretical complications and one case report of trauma following a fall. 8,9 Therefore, headbanding is likely to be safe.…”
Section: Discussionmentioning
confidence: 99%
“…There is a paucity of literature addressing any adverse effects of brain compression through cranial defects in general, with only theoretical complications and one case report of trauma following a fall. 8,9 Therefore, headbanding is likely to be safe.…”
Section: Discussionmentioning
confidence: 99%
“…[13] While a decompressive craniectomy is usually carried out with a sense of urgency, there is usually a long waiting period before reconstruction is entertained. While waiting to complete a cranioplasty with a considerable delay (1-12 months),[1415] several problems may arise due to the presence of a skull defect. Some of these problems include:…”
Section: Introductionmentioning
confidence: 99%
“…While DC is carried out in an emergent setting, a long and variable period of time goes by before reconstruction is planned, which is largely different going from 1 month to 12 months. [14,15] Recently, several studies have been published in literature about the influence of cranioplasty on clinical outcome. [16][17][18][19][20][21][22][23] In 1977 Yamaura [16] reported that 30% of patients with a depressed skin flap following cranial decompression improved after cranioplasty.…”
Section: Introductionmentioning
confidence: 99%
“…[23] Others studies have shown that early cranioplasty would limit complications as hydrocephaly and epilepsy and improve neurological outcome allowing faster recovery. [1,14,15,[21][22][23] Up-to-date the main indication for cranioplasty still remains the direct brain protection from external injuries, the acceleration of patient's rehabilitation, to avoid the new onset of psychological problems due to poor cosmesis. Finally, it should bear in mind, the potential risks and elevated costs of a second and unavoidable procedure as cranioplasty.…”
Section: Introductionmentioning
confidence: 99%